Analisis Produktivitas Proses Produksi Menggunakan Metode Ojective Matrix (OMAX) Pada UMKM Rizki Konveksi - Ismail Irsyad Hakan; Eli Mas’idah; Dana Prianjani (PT. Hasba Edukasi Mandiri, 2025)
In the midst of rapid globalization and technological advances, companies are required to adapt to maintain competitiveness, one of which is through increasing productivity and operational effectiveness. MSME Rizki Konveksi faces challenges in meeting production targets due to the discrepancy between order volume and labor availability, especially in the screen printing and sewing divisions. This research aims to: (1) measure the level of productivity using the Objective Matrix (OMAX) method, (2) identify the factors causing the decline in productivity using the Fishbone Diagram, and (3) develop proposals for improvement using the 5W+1H approach. Based on productivity measurements for the period April–September 2024 using the OMAX method, performance productivity shows a fluctuating trend. The month of April is set as standard (base) conditions. Increased productivity occurred in June (0.901%) and July (1.180%). In contrast, a decline in productivity was detected in May (-0.620%), August (-0.412%), and September (-0.067%). Fishbone analysis shows that the decline is influenced by human factors (lack of labor when overloaded) and work methods. As a follow-up, this research develops an operational improvement strategy using the 5W+1H matrix to minimize production constraints and increase the stability of the company's productivity in the future.